Rancang Bangun Sistem Informasi Pengelolaan Berkas Pada Kantor Notaris/PPAT I Gusti Rai Daniel Ari Putra, SH., M.KN - Welda Welda; Desak Made Dwi Utami Putra; Ayu Manik Dirgayusari (INFORMAL: Informatics Journal, 2020)
Notary Office / PPAT I Gusti Rai Daniel Ari Putra, SH., M.Kn. is a Land Deed Making Official who makes deeds related to land. In carrying out this work, records are still carried out manually, namely still using a recording system in the book which consists of a file monitoring management process, payment for services, and does not provide information regarding the reporting of files that have been completed. This results in each service requiring time from the time the application is submitted to the completion of the file, besides that proof of payment for services can be lost if not recorded. Based on these problems, needed a system to facilitate the management of the file being executed and facilitate business processes that exist in this study created a system with the title Design of Information System File Management in the Office of Notary / PPAT which include data management of the applicant, the data in the file status request , payments and report. This research process uses a linear sequential model method, starting from determining needs, analyzing needs and designing CDM and PDM for the next steps. Furthermore, the authors build and design a system using the PHP programming language and MySQL as a database. The final result of this research is a file management information system at the Notary Office I Gusti Rai Daniel Ari Putra, SH., M.Kn. and testing has been carried out on the system using black box testing whose results are in accordance with the system design.